The best American short stories 2003 - Fox, Joe.; Kenison, Katrina; LeBow, Will.; Mosley, Walter.; Row, Jess.; Simpson, Mona.; Weaver, Rose.; Wyman, Oliver. (Best American series, 2002)
Presents selections from the 2002 edition of Best American Short Stories.